Geochemistry and Isotopic Characteristics of Apatite and Zircon From Late Jurassic Granites in the Jiaobei Terrane, East China: Implications for Petrogenesis and Geodynamic Setting - Mao, Xiancheng; Qu, Xin; Liu, Zhankun; Huang, Jixian; Hollings, Pete; Du, Peijie; Yang, Haibin (Frontiers in Earth Science, 2022)
The North China Craton (NCC) was stable for more than 2.0 Gyr before a Jurassic–Cretaceous large-scale lithospheric thinning event, but the geodynamic setting during the early phases (Late Jurassic) of NCC reworking remains controversial. We present new petrological and whole-rock geochemical data, zircon and apatite geochemistry, U–Pb ages, O isotopic data, and Sr–Nd isotopic data for two phases of Late Jurassic granite (Linglong and Luanjiahe) from the Jiaobei terrane, southeastern NCC. LA-ICP-MS zircon U-Pb dating suggests that the Linglong granite formed about 6 Myr earlier than Luanjiahe granite (158 Ma vs. 152 Ma), after the inception of the paleo-Pacific plate subduction. High zircon U/Yb ratios, high δ18O values (7.89 ± 0.10‰ to 7.67 ± 0.14‰ (2σ)), and inherited zircon age spectra, as well as high apatite F/Cl ratios and Sr–Nd isotopic compositions suggest that the Linglong and Luanjiahe granites formed by partial melting of ancient thickened lower continental crust of the NCC and Yangtze Craton. Magma evolution modeling based on Rb and Rb/Nb data suggests a similar decoupled assimilation-fractional crystallization process for the generation of Linglong and Luanjiahe granite but with different assimilation degree. The water contents of parental magma evaluated by using whole-rock Ba, Sr and apatite F, Cl data indicate that the Linglong granite was formed in a relatively water-rich environment than Luanjiahe. This is consistent with the presence of amphibole and minor negative Eu anomalies in the Linglong granite, as water input can promote amphibole fractionation and suppresses plagioclase crystallization. Considering the similar magma sources but distinct water contents of the granites, and the oblique Paleo-Pacific plate subduction setting in the Late Jurassic, the fluids were likely released from the ocean plate beneath a stacked thickened crust. Since the earliest mafic dikes (OIB-type) in the NCC are coeval with the Luanjiahe granite, we suggest that the lower water contents of the Luanjiahe granite were associated with roll-back that resulted in an increasing distance from slab to continental crust. Such a tectonic transition from subduction compression (158 Ma) to initial extension (152 Ma) in the Late Jurassic perhaps possibly marks the beginning of the reworking of the NCC.